SURAT KETERANGAN TANAH: ANTARA REALITAS DAN PENGAKUAN - FH UBB, Pusat Kajian Agraria (PROGRESIF: Jurnal Hukum, 2017)
The title of land rights in the form of letters made by notaries or sub-district heads with a variety of forms intended to create written evidence of lands controlled by citizens. The issuance of evidence of land acquisition there is made on the land that has not been converted or the lands controlled by the State and then the land is occupied by the community either intentionally or regulated by the Village Head and authorized by the Camat, as if the land has been Is a person's right or belongs to the category of customary rights. In its development the land title is known as Land Certificate. The subdistrict certi fi cate of the land is required as a basis for the rights to the transfer of uncertified lands which are still State lands which may be diverted or disadvantaged by or in the presence of the camat commonly referred to as a waiver of compensation. The camat's certificate of land is the base of the right to be used when it will be proposed to improve the status of the land into a certificate of land right at the local Land Office